Acoustic Tracking System for Autonomous Robots Based on TDE and Signal Intensity - Lasso L., Edgar D.; Patarroyo Sánchez, Alejandra; Martínez S., Fredy H. (TECCIENCIA, 2015)
This article details the development and evaluation of an autonomous acoustic localization system for robots based on Time Delay Estimation (TDE) and signal intensity, principally aimed at robotic service applications. Time Delay Estimation is carried out through an arrangement of two microphones. The time delay criteria are supported with the signal intensity of a third microphone (coplanar arrangement), which permits discerning precisely the location of the source. This third microphone also feeds a voice identification system, which lets the system respond only to specific voice commands. The prediction algorithm operates by comparing the sensed TDE against the theoretical values of the acoustic propagation model, results that are then weighted according to the signal’s mean intensity. A broad set of laboratory experiments is reported on a real prototype that support the system’s performance, showing average errors of Azimuth of 18.1 degrees and elevation of 7.6 degrees. Particularly, the analysis conducted for the estimation permits defining the necessary and sufficient conditions to establish in real time a single position in the space of origin, with sufficient precision for autonomous navigation applications